Design with the Desert Conservation and Sustainable Development - Malloy, Richard; Brock, John; Floyd, Anthony; Livingston, Margaret; Webb, Robert H. (Taylor & Francis, 2013)
Typical development in the American Southwest often resulted in scraping the desert lands of the ancient living landscape, to be replaced with one that is human-made and dependent on a large consumption of energy and natural resources. This transdisciplinary book explores the natural and built environment of this desert region and introduces development tools for shaping its future in a more sustainable way. It offers valuable insights to help promote ecological balance between nature and the built environment in the American Southwest-and in other ecologically fragile regions around the world.